VARIABILITY STUDIES IN M3 GENERATION IN BLACKGRAM (VIGNA MUNGO (L.)HEPPER) - M. P. MESHRAM,; R. I. ALI,; A. N. PATIL,; MEENA, SUNITA (The Bioscan, 2013)
In the present study, pure line seeds of black gram variety viz. T-9, TPU-4 and one promising genotype AKU-18 was treated with gamma irradiation (15kR, 25kR and 35kR) with the objective to assess the variability in M3 generation.. Highest GCV and PCV and high estimates of heritability were recorded for the characters sprouting percentage, number of pods plant-1 and grain yield plant-1 (g). High heritability accompanied with high genetic advance was recorded for number of pods plant-1 governed by additive gene effects and therefore selection based on phenotypic performance will be useful to improve character in future.